2013
DOI: 10.3813/aaa.918598
|View full text |Cite
|
Sign up to set email alerts
|

Silent Owl Flight: Comparative Acoustic Wind Tunnel Measurements on Prepared Wings

Abstract: The wings and feathers of most genera of owls showu nique properties that are held responsible for the silent flight of the owls. This ability to fly silently has long been of interest for engineers, with the aim to transfer the basic noise reducing mechanisms to technical applications such as blades of fans and propellers. The present paper describes acoustic and aerodynamic wind tunnel measurements on prepared bird wings of different species, among them twosilently flying species of owls, the barn owl( Tyto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Circular and rectangular nozzles of different contraction ratios can be interchanged, which produce approximately 0.2% and 0.1% freestream turbulence intensities, respectively. Many airfoil self noise studies have already been performed in this facility 11,12 . The University of Adelaide from Australia built an aeroacoustic wind tunnel facility which is situated in an 8 m 3 cubic anechoic chamber with a cut-off frequency at 200 Hz 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Circular and rectangular nozzles of different contraction ratios can be interchanged, which produce approximately 0.2% and 0.1% freestream turbulence intensities, respectively. Many airfoil self noise studies have already been performed in this facility 11,12 . The University of Adelaide from Australia built an aeroacoustic wind tunnel facility which is situated in an 8 m 3 cubic anechoic chamber with a cut-off frequency at 200 Hz 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Mascha and Graham discovered and innovatively concluded three mechanisms of the owl feathers that supposedly enabled the silent flight: (1) comb-like structure at the leading edge of the wings, (2) long and soft fringes at the trailing edge, and (3) soft downy upper surface of the feathers [1,2]. These three mechanisms have been gradually identified [3][4][5][6] and accepted by the bionic researchers [7][8][9][10][11][12][13]. The reported biological studies of the noiselessly flying owls show that owl wing feather has significantly long soft feather material and unique morphological structure, which are different from other bird feathers.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the wings from the two owl species tested generated less noise per unit lift force than the wings of non-silent flyers. Geyer et al [29] further compared the aerodynamic performance of prepared wings at 0.5 spanwise position. It was found that the wings of the two owl species tested produced about 5-10 dB less noise than the other wings at higher Strouhal numbers (1000 in their case (fig.…”
Section: Noise Production In Owls Compared With Noise Production In Omentioning
confidence: 99%
“…Thus, the authors concluded that the velvety surfaces stabilize the flow field at low Reynolds numbers, enabling the owl to fly more slowly and thus more silently. Following the observations by Geyer et al [29], Clark et al [61] performed experiments to examine the noise radiated by vertical filaments that form a canopy above a surface (figure 5c). This structure reduced pressure fluctuations on the underlying surface.…”
Section: Serrationsmentioning
confidence: 99%
See 1 more Smart Citation